2015
DOI: 10.4103/1947-2714.168678
|View full text |Cite
|
Sign up to set email alerts
|

Septic arthritis in the temporomandibular joint

Abstract: Septic arthritis of the temporomandibular joint (TMJ) is a rare event that has only been reported a few dozen times worldwide. This case is remarkable for septic arthritis of the TMJ joint in an otherwise healthy male.Case Report:A 24-year-old male presented to the emergency department with periauricular swelling, erythema, fever, myalgia's and generalized joint pain. He had previously sought medical attention and was placed on ciprofloxacin. However, he developed facial swelling and a rash and had to disconti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 9 publications
(10 reference statements)
0
13
0
Order By: Relevance
“… 8 , 12 If initial CT imaging is negative and clinical suspicion remains high, magnetic resonance imaging should be performed. 15 …”
Section: Discussionmentioning
confidence: 99%
“… 8 , 12 If initial CT imaging is negative and clinical suspicion remains high, magnetic resonance imaging should be performed. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Once SATMJ is suspected, joint aspiration is recommended to confirm it. The aspirated fluid and turbidity are required to be grossly examined for color as well as subjected to Gram staining, culture and sensitivity analysis ( 29 , 38 ). Owing to their relatively high accuracy and the high rate of the occurrence of bacteria in the synovial fluid, cultures are considered to be a credible method to definitively diagnose SATMJ, but not gonococcal arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing body of evidence suggested that the detection of pathogens by microbiological culture is important for selecting a suitable and efficient antibiotic therapy ( 5 , 10 , 13 , 27 , 29 , 30 , 38 , 40 ). Although empiric antibiotic therapy may not be effective against certain pathogens, systemic antibiotics should be applied if a provisional diagnosis of SATMJ has been made, and a negative result of definitive bacterial culture should not delay early vigorous treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Septic arthritis of the temporomandibular joint (TMJ) is a rare condition that occurs by seeding pathogens, typically bacteria, by hematogenous route or by direct spread into the joint (1)(2)(3)(4)(5)(6). Unlike osteoarthritis of the joint that is considered "low inflammatory" arthritis, septic TMJ arthritis is considered a "high-inflammatory" arthritis and exhibits distinct biological and clinical behavior (6,7).…”
Section: Introductionmentioning
confidence: 99%